Pharmacoeconomics in Africa: needs, prospect and challenges - Temitope Ben-Ajepe; Ifechukwu Benedict Nwogu; Damilola Quazeem Olaoye; Abdulhafeez Ayodele Mustapha; Theogene Uwizeyimana; Yusuff Adebayo Adebisi (Taylor & Francis Group, 2021)
Africa as a continent has experienced a continuous increase in the cost of healthcare as its demands increase. With many of these African countries living below the poverty threshold, Africans continue to die from preventable and curable diseases. Population increases have led to an increase in demands for healthcare, which unfortunately have been met with inequitable distribution of drugs. Hence, the outcomes from healthcare interventions are frequently not maximized. These problems notably call for some economic principles and policies to guide medication selection, procurement, or donation for population prioritization or health insurance. Pharmacoeconomics drives efficient use of scarce or limited resources to maximize healthcare benefits and reduce costs. It also brings to play tools that rate therapy choice based on the quality of life added to the patient after a choice of intervention was made over an alternative. In this paper, we commented on the needs, prospect, and challenges of pharmacoeconomics in Africa.